Monitoring, investigation compliance (MIC) & corporate image of Dhaka stock exchange - Haider, H. M. SIbbir (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015